Keeping it practical and keeping it simple. (12th December 2017) - Nation, Paul
Abstract : When I look back over my career as a teacher-trainer and researcher, I can see two themes that run through my work. The first theme is my concern for the practical issues of teaching English as a foreign language (EFL), with the strong proviso that practice must be based as far as possible in research. For me this represents theapplied in applied linguistics. The second theme is a concern for seeing what the parts are that make up the whole. I think underlying this concern is the desire to see the principles governing the way the parts go together, and underlying this is a tendency to want to see what is simple and rule-based. Knowledge needs to be communicated to others and this is best done if we are aware of the important basic principles and components, and can present them as simply as possible.